2021
DOI: 10.3390/cells10123352
|View full text |Cite
|
Sign up to set email alerts
|

Role of ADGRG1/GPR56 in Tumor Progression

Abstract: Cellular communication plays a critical role in diverse aspects of tumorigenesis including tumor cell growth/death, adhesion/detachment, migration/invasion, angiogenesis, and metastasis. G protein-coupled receptors (GPCRs) which constitute the largest group of cell surface receptors are known to play fundamental roles in all these processes. When considering the importance of GPCRs in tumorigenesis, the adhesion GPCRs (aGPCRs) are unique due to their hybrid structural organization of a long extracellular cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 105 publications
(199 reference statements)
0
3
1
Order By: Relevance
“…Furthermore, we identi ed subgroups of genes that may contribute to nintedanib resistance. Correlation analysis with lung function suggested that the gene ADGRG1 may be responsible for nintedanib resistance.ADGRG1/GPR56 is a type of tumorassociated aGPCR that is thought to be a potential biomarker and prognostic factor for speci c cancer types due to its tumor-inhibitory and tumor-promoting functions (54).However, our analysis using the TCGA database did not show a correlation between ADGRG1 and survival in lung cancer patients. This suggests that there could be differences in the treatment effects of ADGRG1 and nintedanib, highlighting the need for further research in this area.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, we identi ed subgroups of genes that may contribute to nintedanib resistance. Correlation analysis with lung function suggested that the gene ADGRG1 may be responsible for nintedanib resistance.ADGRG1/GPR56 is a type of tumorassociated aGPCR that is thought to be a potential biomarker and prognostic factor for speci c cancer types due to its tumor-inhibitory and tumor-promoting functions (54).However, our analysis using the TCGA database did not show a correlation between ADGRG1 and survival in lung cancer patients. This suggests that there could be differences in the treatment effects of ADGRG1 and nintedanib, highlighting the need for further research in this area.…”
Section: Discussioncontrasting
confidence: 55%
“…Supported by earlier knock-out studies [ 17 , 27 , 30 , 32 ] and the evaluation of multiple mouse genes in collagen-dependent thrombus formation in vivo and in vitro [ 14 ], our findings now add another element to the complex signaling cascades in platelets required for the build-up of a stable contracted thrombus. Our work also extends the multitude of functions of GPR56 in immune regulation and tumor progression [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 54%
“…Besides, ZAR1L has been suggested potential associated with tumor suppressors, which can repress the transcription of BACA2 to repress breast cancer cells 41 . ADGRG1 (GPR56) is a representative tumor-related G protein-coupled receptors (GPCRs) member, which plays an important role in tumor cell growth, migration, angiogenesis, and metastasis 42,43 . AK7 is known to maintain ciliary structure and function whose dysfunction may lead to primary ciliary dyskinesia including bronchiectasis and reduced fertility [44][45][46] .…”
Section: Discussionmentioning
confidence: 99%